Developing tough terpolymer hydrogel with outstanding swelling ability by hydrophobic association cross-linking. (21st July 2022) - Rahmani, Pooria; Shojaei, Akbar
Abstract: Hydrogels with remarkable hydrophilicity and tunable toughness are appealing materials to serve as superabsorbent polymers. However, chemically cross-linked hydrogels often suffer from low toughness regardless of their considerable swelling, restricting their widespread applications. In comparison, the network of physically cross-linked hydrogels can be regulated to meet both a high swelling ratio and considerable toughness. Here, we develop superabsorbent and tough hydrophobic associated hydrogels using terpolymerization of poly acrylic acid (PAA), polyacrylamide (PAM), and lauryl methacrylate (LMA) within the micelles formed by sodium dodecyl sulfate (SDS) surfactant. To this end, various parameters such as AA/AM molar ratio, the concentration of hydrophobic and hydrophilic monomers in the hydrogel network were optimized by morphological, mechanical, rheological, and swelling studies. The multiple physical interactions inside the hydrogel endow it with suitable mechanical properties (stretchability 1500–3000%, tensile strength 50–150kPa, and toughness up to 2.4 MJ/m3). On the other hand, the macroporous network of the hydrogels caused by the hydrophobic association is responsible for their outstanding swelling ratio. On this basis, the hydrogels can absorb water up to 1000 g/g while keeping their 3D network noticeably, exceeding the swelling degree of hydrophobic associated hydrogels reported till now. Such a fascinating feature can widen the hydrogels' applications in various areas. Graphical abstract: Image 1 Highlights: Terpolymer hydrogels with high swelling ratio and superior toughness were synthesized. AA/AM ratio, hydrophobic and hydrophilic monomer contents were adjusted to obtain mechanical and swelling properties. Hydrophobic cross-linked centers render remarkable toughening to the hydrogels. Hydrogels with a 3-D network and microporous structure revealed outstanding swelling. Structural stability of the hydrogels and their reusability are beneficial for their practical applications.